Quality of life, related to oral healthcare, in the Elderly Center de San Isidro, Lima - Diego Alonso Kurt Espinoza-Espinoza; David Soto-Peñaloza; Carmen Rosa García-Rupaya; Daniel Alonso Kim Espinoza-Espinoza; Julissa Amparo Dulanto Vargas; Rafael Morales-Vadillo (Editorial Ciencias Médicas, 2022)
Introduction: Maintaining quality of life is one of the most important results of care services. Several plans support the importance of measuring it in older adults. Objective: To assess oral health-related quality of life in members of a senior center in Lima, Peru. Methods: A descriptive cross-sectional study was carried out in a population of 1800 older adults. The sample consisted of 184 participants. The oral health impact profile instrument (OHIP14sp) was used to measure quality of life in relation to oral health. Content validity was performed by a group of evaluators and the consistency of the questionnaire was evaluated with Cronbach's alpha test. The information was summarized in percentages and Fisher's and chi-square hypothesis tests were used to identify the relationship of quality of life with gender and age, and Poisson regression. Results: The quality of life of older adults was poor in 9.8%, good in 23.4%, and excellent in 66.8%. Women (71%) had a better quality of life than men (58%). It was observed that the younger the age, the better the quality of life. Most of the adults were able to perform their daily activities except for 7.1%. Oral health did not have a negative impact on the quality of life of older adults in terms of psychological discomfort, functional limitation and handicap, only 61%, 49% and 17%, respectively. Conclusions: The impact on oral health in Lima identified as excellent or regular the quality of life in relation to oral health of older adults attending the San Isidro Senior Center.